Evaluation of porcine immune responses among different genetic groups - Jeeeba K George (Department of Animal Breeding and Genetics, College of Veterinary and Animal Sciences, 2005)
Porcine immune responses were evaluated using PHA skin test and microhaemolytic assay in this study. Investigation was undertaken in three genetic groups namely Desi, Large White Yorkshire and Duroc x Large White Yorkshire. The economic traits studied were birth weight, litter size at birth, weaning litter size and weaning body weight. The cell-mediated immune response was assessed by noting cutaneous response to intradermal injection of phytohaemagglutinin. Humoral immune response was assessed by noting antibody response to sheep red blood cells. Correlation of immune response with growth, disease occurrence and mortality among the littermates were also evaluated. The highest birth weight, body weight at weaning, litter size at birth and weaning were recorded in Duroc x Large White Yorkshire, medium in Large White Yorkshire and least in Desi. The increase in skin thickness at 24, 48 and 72 hour post- injection of PHA-M was highest in Desi, medium in Duroc x Large White Yorkshire and least in Large White Yorkshire. The correlations of cutaneous response to phytohaemagglutinin with pre- weaning mortality among littermates and enteritis were found to be non-significant in Desi, Large White Yorkshire and Duroc x Large White Yorkshire piglets. Among three genetic groups, serum samples from Desi piglets had a higher mean antibody titre on 7th, 14th, 21st day than the other two. Medium titre was noted in Duroc x Large White Yorkshire and least in Large White Yorkshire. Sire effect was highly significant with antibody response on seventh, fourteenth and 21st day post inoculation. The correlations of antibody response to sheep RBC with pre- weaning mortality among littermates and enteritis were also found to be non-significant in Desi, Large White Yorkshire and Duroc x Large White Yorkshire piglets. The effects of sires within Desi, Large White Yorkshire and Duroc x Large White Yorkshire were found to be highly significant (P<0.01) on antibody response to sheep RBC on 7th, 14th and 21st day. Different litter traits had no significant effect on cutaneous response to PHA-M and antibody response to sheep RBC. High heritabilities were estimated for pre-injection skin thickness, cutaneous response to PHA-M at 24, 48, 72 hour post-injection and antibody response to sheep red blood cells on 7th, 14th, 21st day post- inoculation. Correlations of antibody response to sheep RBC on 14th day with cutaneous response to phytohaemagglutinin at 24 hour and 48 hour were found to be non-significant. Antibody response to sheep RBC on 21st day correlated non-significantly with cutaneous response to PHA-M at 24 hour and 48 hour. Antibody response to sheep RBC on 7th, 14th and 21st day associated non-significantly with weaning body weight and pre-weaning mortality. Even though correlations were non-significant, they revealed a negative trend. The association between cutaneous response to PHA-M at 24 hour and birth weight was non-significant.